Проект "Базового словника російської мови" - Шведова, М. (Лексикографічний бюлетень, 2015)
The Basic Russian dictionary is a description of the most frequent Russian lexical units within their respective semantic and grammatical relationships. Th e dictionary is intended for foreign students of Russian. In the fi rst part of the dictionary the word list is represented as a thesaurus, that is, as a set of tables representing each a semantic fi eld of words. Each word is marked by a frequency index. In the second part of the dictionary the same words are given in the alphabetical order accompanied by an extended lexicographical description. In the descriptions only the simplest grammatical constructions and frequent words are used.